2020
DOI: 10.1101/2020.11.12.380626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SAM homeostasis is regulated by CFIm-mediated splicing of MAT2A

Abstract: SUMMARYS-adenosylmethionine (SAM) is the methyl donor for nearly all cellular methylation events. Cells regulate intracellular SAM levels through intron detention of the MAT2A RNA, which encodes only SAM synthetase expressed in most cells. The N6-adenosine methyltransferase METTL16 promotes splicing of the MAT2A detained intron by an unknown mechanism. Using an unbiased CRISPR knock-out screen, we identified CFIm25 (NUDT21) to be a regulator of MAT2A intron detention and intracellular SAM levels. CFIm25 is a c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(139 reference statements)
1
2
0
Order By: Relevance
“…4A-B), which is consistent with the study by Pendleton et al [23]. It has been reported that METTL16 had a limited number of validated direct targets, including MAT2A mRNA, U6 snRNA and long non-coding RNA (lncRNA) MALAT [30,31], which distinguishes it from the METTL3/METTL14 complex, who modi es most m 6 A sites on RNA [24,32]. Therefore, the knockdown of METTL16 is unlikely to reduce the overall levels of m 6 A by directly affecting the number of m 6 A modi cations in its target RNAs.…”
Section: Knockdown Of Mettl16 In the Hippocampi Disrupts Hippocampal ...supporting
confidence: 89%
See 1 more Smart Citation
“…4A-B), which is consistent with the study by Pendleton et al [23]. It has been reported that METTL16 had a limited number of validated direct targets, including MAT2A mRNA, U6 snRNA and long non-coding RNA (lncRNA) MALAT [30,31], which distinguishes it from the METTL3/METTL14 complex, who modi es most m 6 A sites on RNA [24,32]. Therefore, the knockdown of METTL16 is unlikely to reduce the overall levels of m 6 A by directly affecting the number of m 6 A modi cations in its target RNAs.…”
Section: Knockdown Of Mettl16 In the Hippocampi Disrupts Hippocampal ...supporting
confidence: 89%
“…METTL16 does not form complexes with other m 6 A methyltransferases, unlike METTL3 and METTL14, and has a limited number of m 6 A modi cation targets, including MAT2A mRNA, U6 snRNA, and lncRNA MALAT [30,31]. Interestingly, knockdown of METTL16 was found to reduce the overall levels of m 6 A [23],…”
Section: Discussionmentioning
confidence: 99%
“…S-adenosylmethionine (SAM) is a methyl donor for almost all cell methylation events. Scarborough et al (2021) reported that NUDT21 regulates intracellular SAM levels. As shown, m 6 A RNA methylation modification plays a key role in mRNA splicing, suggesting that the m 6 A markers identified in this study are closely related to the m 6 A modification process.…”
Section: Discussionmentioning
confidence: 99%